2019
DOI: 10.1097/dss.0000000000002294
|View full text |Cite
|
Sign up to set email alerts
|

Demographics of Men and Minorities in Cosmetic Clinical Trials of Botulinum Toxin and Hyaluronic Acid Fillers

Abstract: BACKGROUND The demographics of men and minorities in clinical studies of nonsurgical cosmetic procedures have not been well described. There is a growing interest in nonsurgical cosmetic procedures. The patients studied in clinical trials may not be reflective of the real-world demographic of patients seeking nonsurgical cosmetic procedures. OBJECTIVE To examine the demographics of men and minorities in clinical studies of nonsurgical cosmetic procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…50 Moreover, in a justpublished meta-analysis of 41 clinical trials on nonsurgical cosmetic procedures, women accounted for 88.2% of all patients. 51 Unfortunately, but consistent with their disproportionate representation among CS patients, most published studies on attitudes toward and predictors of CS have been restricted to all-female 8,9,38,41,43,44,52,53 populations, with a few others restricted to men. 23,54,55 In the few studies in which women and men were compared directly, women have tended to be more knowledgeable of CS than men, 13 and generally be more accepting.…”
Section: Gendermentioning
confidence: 99%
“…50 Moreover, in a justpublished meta-analysis of 41 clinical trials on nonsurgical cosmetic procedures, women accounted for 88.2% of all patients. 51 Unfortunately, but consistent with their disproportionate representation among CS patients, most published studies on attitudes toward and predictors of CS have been restricted to all-female 8,9,38,41,43,44,52,53 populations, with a few others restricted to men. 23,54,55 In the few studies in which women and men were compared directly, women have tended to be more knowledgeable of CS than men, 13 and generally be more accepting.…”
Section: Gendermentioning
confidence: 99%
“…Botulinum toxin and dermal fillers are the 2 most popular nonsurgical cosmetic procedures performed globally to treat age-associated changes and are often used in combination. 2 There are many kinds of filler materials for volume replacement and enhancement, such as hyaluronic acid (HA), 3 collagen, poly- l -lactic acid, 4 and calcium hydroxylapatite. 5 , 6 These fillers can be used for cheek and chin augmentation, nose reshaping, midface volumization, and lip enhancement.…”
mentioning
confidence: 99%
“…In a systematic review published in 2020, Roman and Zampella reported that men on average represented only 13.9% of all participants in the randomized controlled clinical trials conducted of botulinumtoxinA for cosmetic indications. 23 …”
mentioning
confidence: 99%